Challenges and Opportunities in Relation to Sargassum Events Along the Caribbean Sea - Robledo, Daniel; Vázquez-Delfín, Erika; Freile-Pelegrín, Yolanda; Vásquez-Elizondo, Román Manuel; Qui-Minet, Zujaila Nohemy; Salazar-Garibay, Adán (Frontiers in Marine Science, 2021)
Mass blooms and stranding of pelagic Sargassum spp. in the Atlantic, termed Sargassum events are becoming more frequent in response to several factors: nutrient enrichment, increased temperature, changes in climatological patterns, but some causes remain unknown. The magnitude of Sargassum events in the Caribbean Sea since 2011 make us aware of the necessity to tackle these events, and macroalgal blooms generally, not only locally but on a regional scale. At least three pelagic species of Sargassum have been dominant in the blooms that have occurred along Caribbean coastlines in great quantities. Due to the regional scale of these events and its complexity, its management should be based on basic and applied information generated by different collaborative actors (national and international) through interdisciplinary and transdisciplinary work. To address this, we propose different phases (exploratory, valorization, and management) and the approach for their study should include detection, collection, stabilization and experimentation. This information will help identify the potential applications and/or ecological services to develop for the exploitation and mitigation strategies in the region. Relevant challenges and opportunities are discussed, remarking on the necessity to evaluate the spatiotemporal variation in the abundance and chemical composition of floating and stranded biomass. The above-mentioned will provide management strategies and economic opportunities as possible solutions to their extensive impact in the Caribbean.